Didang decoction attenuates cancer‐associated thrombosis by inhibiting PAD4‐dependent NET formation in lung cancer - Xiaoyan Zeng; Jiuxi Li; Liyuan Pei; Yaping Yang; Ya Chen; Xuejing Wang; Ting Zhang; Ting Zhou (Pulmonary Circulation)
Abstract This research aims to investigate the impact of Didang decoction (DD) on the formation of neutrophil extracellular traps (NETs) and cancer‐associated thrombosis in lung cancer. BALB/c nude mice were used to establish xenograft models for inducing deep vein thrombosis. Tumor growth and thrombus length were assessed. The impact of DD on NET generation was analyzed using enzyme‐linked immunosorbent assay, immunofluorescence staining, quantitative real‐time PCR, and western blot analysis, both in vivo and in vitro. CI‐amidine, a PAD4 inhibitor, was employed to evaluate the role of PAD4 in the generation of NETs. In vivo studies demonstrated that treatment with DD reduced tumor growth, inhibited thrombus formation, and decreased the levels of NET markers in the serum, tumor tissues, neutrophils, and thrombus tissues of mice. Additional data indicated that DD could suppress neutrophil counts, the release of tissue factor (TF), and the activation of thrombin‐activated platelets, all of which contributed to increased formation of NETs in mouse models. In vitro, following incubation with conditioned medium (CM) derived from Lewis lung carcinoma cells, the expression of NET markers in neutrophils was significantly elevated, and an extracellular fibrous network structure was observed. Nevertheless, these NET‐associated changes were partially counteracted by DD. Additionally, CI‐amidine reduced the expression of NET markers in CM‐treated neutrophils, consistent with the effects of DD. Collectively, DD inhibits cancer‐associated thrombosis in lung cancer by decreasing PAD4‐dependent NET formation through the regulation of TF‐mediated thrombin‐platelet activation. This presents a promising therapeutic strategy for preventing and treating venous thromboembolism in lung cancer.